2018
DOI: 10.1021/acs.iecr.8b03864
|View full text |Cite
|
Sign up to set email alerts
|

Fast and High Amount of U(VI) Uptake by Functional Magnetic Carbon Nanotubes with Phosphate Group

Abstract: In the present study, PZS-TPP/CNT/Fe 3 O 4 was fabricated by carbon nantubes (CNTs) with polyphosphazene and magnetic particles for application in U(VI) removal. The structure of the synthesized composite was characterized by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), a vibrating sample magnetometer (VSM), and X-ray photoelectron spectroscopy (XPS). Studies of the effects of pH values, U(VI) concentration, contact time, and adsorption temperature including competing ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The results reveal that the isotherm fits better to the Langmuir model ( R 2 = 0.994) than to the Freundlich model ( R 2 = 0.941) . Moreover, the maximum uranium adsorption amount of HCPP (800 mg g –1 ) calculated by the Langmuir adsorption equation is much closer to the corresponding experimental data (750 mg g –1 ). It can be clearly concluded that the adsorption of uranium on HCPP follows the Langmuir adsorption model . The comparison of uranium adsorption capacity obtained in this work with those of other adsorbents is represented in Table .…”
Section: Resultssupporting
confidence: 59%
“…The results reveal that the isotherm fits better to the Langmuir model ( R 2 = 0.994) than to the Freundlich model ( R 2 = 0.941) . Moreover, the maximum uranium adsorption amount of HCPP (800 mg g –1 ) calculated by the Langmuir adsorption equation is much closer to the corresponding experimental data (750 mg g –1 ). It can be clearly concluded that the adsorption of uranium on HCPP follows the Langmuir adsorption model . The comparison of uranium adsorption capacity obtained in this work with those of other adsorbents is represented in Table .…”
Section: Resultssupporting
confidence: 59%
“…The saturated U­(VI) adsorption capacities of pure carbon nanotubes (CNTs) and graphene oxide are around 41.48 and 97.5 mg·g –1 , respectively. , Therefore, many improved methods were already proposed to optimize the solution to the problems mentioned above. For example, Liu et al prepared a magnetic phosphoryl functional polyphosphazene base built with a CNT composite (PZS-TPP/CNT/Fe 3 O 4 ), which had an optimal adsorption of 300 mg·g –1 for U­(VI) removal. Zhu et al grafted fungus hypha onto a layer of two-dimensional graphene oxide sheets and pyrolyzed to form a fungal hyphae/graphene oxide aerogel for efficient removal of U­(VI) with an increased adsorption capacity (288.42 mg·g –1 ).…”
Section: Introductionmentioning
confidence: 99%
“…29 In addition, functionalized PPZs were prepared by polymerization precipitation with p -phenylenediamine, polyethyleneimine and 4,4′-oxydianiline for uranyl recovery, respectively, showing promising adsorption performance. Their adsorption capacities for uranium ions were 168.9 mg g −1 , 30 273.5 mg g −1 , 31 and 606.1 mg g −1 , 32 respectively. These findings reveal that the substitution of the side groups of HCCP by different amino ligands affects the uranium-binding capacity of PPZs.…”
Section: Introductionmentioning
confidence: 99%